Application of Large-Scale 3D Non-Orthogonal Boundary Fitted Sediment Transport Model and Small-Scale Approach for Offshore Structure in Cimanuk Delta North Java Sea - Muin, Muslim; Idris, Krisnaldi; Yuanita, Nita (ITB Journal Publisher, LPPM ITB, 2016)
The morphology of the Cimanuk Delta at the North Java Sea has changed rapidly over the last two decades. The annual sediment deposition is about two million cubic meters (Yuanita and Tingsanchali, [1]). The large-scale ocean hydrodynamics and sediment transport model MuSed3D (Muin, [2]) was applied to the North Java Sea to simulate suspended sediment transport at the study site. A potential offshore structure was positioned at approximately 30 km from the Cimanuk Delta. The result of the large-scale model was calibrated using observation data and Landsat satellite image interpretation. The agreement between the modeling results and the observations was excellent. It was found that the critical shear stresses for erosion and deposition were 0.1 Pa and 0.05 Pa respectively. An empirical formula was further utilized to assess the local scouring at the potential offshore structure site in a small-scale domain and under extreme conditions.